Penerapan Model Pembelajaran Kooperatif TPS untuk Meningkatkan Hasil Belajar Siswa Kelas IX SMP Negeri 1 Babalan - Anisa Fitria (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The objectives of this study are to: (1) Describe the improvement of student learning outcomes through the application of the TPS cooperative learning model in grade IX SMP Negeri 1 Babalan. (2) Improve student learning outcomes through the application of the TPS cooperative learning model with a minimum of classical completion. This type of research is Classroom Action Research (PTK) or action research which consists of 2 cycles, where each cycle consists of 1 meeting. The subjects in this study were grade IX-5 students of SMPN 1 Babalan consisting of 32 students. From the results of the study, it can be concluded that the following things are: (1) There is an increase in student mathematics learning outcomes. The percentage of completeness classically increased from the initial test of 21.87% then during cycle I which was 62.5% to 87.5% in cycle II, so based on the results of the analysis it was obtained that this study had reached the specified success indicators. (2) After the implementation of the Think Pair Share type cooperative learning model, students' mathematics learning outcomes have been classically completed, namely 87.5%.